Effects of Acetyl-DL-Leucine on Ataxia and Downbeat-Nystagmus in Six Patients With Ataxia Telangiectasia. (January 2022) - Brueggemann, Adriana; Bicvic, Antonela; Goeldlin, Martina; Kalla, Roger; Kerkeni, Hassen; Mantokoudis, Georgios; Abegg, Mathias; Kolníková, Miriam; Mohaupt, Markus; Bremova-Ertl, Tatiana
Background: There is no authorized treatment for ataxia telangiectasia (AT). As cerebellar symptoms of storage diseases were improved by acetyl-DL-leucine (ADLL), the authors hypothesized a symptomatic and disease-modifying effect in AT upon supplementation with ADLL. Methods: Six patients were treated with ADLL 3 g/day for 1 week followed by 5g/day for 3 weeks to 1 year. Cerebellar ataxia was evaluated by validated scales. Gaze-holding, saccades and smooth pursuit were examined by video-oculography. Measurements took place at baseline, at 1 month of therapy in 5 patients, and after 6 and 12 months in 1 patient. Results: The Scale for Assessment and Rating of Ataxia changed from the baseline, mean, (SD, min-max) of 22.1 (5.88, 11-28.5) to 18 points (5.39, 8.5-23.5) after 1 month on medication ( P = .0028). All patients demonstrated gaze-holding deficits; 3 patients had central-position downbeat-nystagmus. Mean slow-phase velocity of this nystagmus with the gaze straight-ahead changed from 5.57°/s (1.8, 3.53-6.99) to 4.7°/s (0.79, 3.97-5.56) after 1 month on treatment (1.35, -2.56-4.17) ( P = .046). Interpretation: ADLL may improve ataxia and ocular stability in AT patients, while the molecular basis still remains to be elucidated. A multicentric, rater-blinded, phase II trial currently investigates the effects of acetyl-L-leucine in AT (NCT03759678).